KINERJA DINAS KESEJAHTERAAN SOSIAL PADA PELAKSANAAN PROGRAM OPERASI DAERAH SELESAIKAN KEMISKINAN DI KOTA BITUNG - TINUNGKI, INDA SARI; RORONG, ARIE; TAMPONGANGOY, DEYSI (Sam Ratulangi University, 2020)
Summary : Poverty is a problem that cannot be postponed to overcome and must be a top priority in theimplementation of social welfare development based on the background of the problem, so this study aimsto find out what the performance of the Social Welfare Service on the Implementation of RegionalOperations Programs to Resolve Poverty in Bitung City. The type of research used in this research is aqualitative approach. This research aims to understand the needs of the poor. The informants in the studywere obtained from field visits to the research location by the researcher, namely in the Social ServiceOffice, the method of determining informants was by selecting sources who really knew about problemsthat occur on the spot so that they will provide information precisely as needed by researchers. The resultsshowed that the preparation of program plans, strategic plans and operational / implementation plans forthe ODSK program by the Social Service of Bitung City. The goal is that the planning of the ODKprogram and its implementation do not overlap but the program runs one way and in harmony startingfrom the provincial central level to the District and Village levels.